The hundred-foot journey [compact disc, unabridged] : a novel - Morais, Richard C., 1960- (Blackstone Audio, Inc., 2012)
Born above his grandfather's modest restaurant in Mumbai, Hassan first experienced life through intoxicating whiffs of spicy fish curry, trips to the local markets, and gourmet outings with his mother. But when tragedy pushes the family out of India, they console themselves by eating their way around the world, eventually settling in a small village in the French Alps. The boisterous Haji family opens an inexpensive Indian cafe opposite an esteemed French restaurant--that of the famous chef Madame Mallory--and infuse the sleepy town with the spices of India, transforming the lives of its eccentric villagers and infuriating their celebrated neighbor. Only after Madame Mallory wages culinary war with the immigrant family does she finally agree to mentor young Hassan, leading him to Paris, the launch of his own restaurant, and a slew of new adventures.